Rational design of TiO₂-nanocarbon hybrids for photocatalytic applications - Al Mayyahi, Ahmed Abdulrazzaq Qasim (Kansas State University, 2023)
Environmental pollution and the subsequent impact on human health are major challenges facing our planet. Photocatalysis is one potential strategy for practical, economical, and effective environmental remediation. Among various photocatalysts, hybrid structures formed by coupling TiO₂ and nanocarbons have shown promise in air purification. However, the activity of currently available TiO₂-nanocarbon hybrids is plagued by the poor interfacial contact between TiO₂ and the nanocarbons, low transparency of the nanocarbons, ineffective adsorption of pollutants on the hybrid photocatalysts, and a large band gap of TiO₂ (3.2 eV), as well as difficulties associated with TiO₂-nanocarbon synthesis. This study (1) demonstrates the rational design of TiO₂-nanocarbon hybrids to overcome the aforementioned challenges and (2) investigates the application of designed photocatalysts in environmental photocatalysis. Among various nanocarbons, metallic carbon nanotubes (CNTs) and MXenes have been widely used as co-photocatalysts with TiO₂. Due to their highly conductive nature and suitable band structure, these nanostructures can accept charge carriers from TiO₂, hindering electron-hole recombination and boosting photocatalytic reaction. The first part of my work demonstrates the design of TiO₂-CNT hybrids with high-quality of interfacial contact and superior photocatalytic activity. We demonstrate that adapting the dimension of CNTs to be compatible with TiO₂ improves the quality of interfacial contact between the two components and provides well-tailored channels for charge carrier shuttling and separation. In this regard, we show that wrapping TiO₂ with short-length CNTs, synthesized by ultrasonication-assisted cutting of long-length CNTs, results in a photocatalyst with higher photocatalytic activity in acetaldehyde oxidation (k = 0.0150 min⁻¹) than the pristine TiO₂ (k = 0.0073 min⁻¹) and conventional photocatalyst prepared by coupling TiO₂ with long CNTs (k = 0.0107 min⁻¹). Interestingly, the activity of TiO₂ coupled with short CNTs outperforms that of state-of-art photocatalyst, TiO₂-nanographene (k = 0.0125 min⁻¹). The second portion of my work investigates the utilization of titanium carbide MXene as a co-photocatalyst with TiO₂. The MXene is not only characterized by its high electrical conductivity (higher than that of CNTs/graphene) but also its unique surface chemistry typified by the presence of abundant functional groups (-F, =O, and -OH). These hydrophilic groups render the facile processibility of MXene via wet chemistry and facilitate its interaction with TiO₂. The same functional groups can also serve as anchors for pollutant adsorption. Nevertheless, MXene derived from the conventional methods is a multilayer structure with low transparency, large size (micro-sized structure), and high concentration of fluorine terminals; these factors are detrimental to the photocatalytic process. On the one hand, the low transparency of MXene hinders light penetration to TiO₂ in the TiO₂-MXene hybrid structure, undermining the charge carrier excitation. On the other hand, the large size of MXene compromises its interaction with TiO₂ while its terminal fluorine groups reduce pollutant adsorption on the resulting hybrid. Therefore, in this project, we demonstrate the intercalation of MXene with tetrapropylammonium hydroxide (TPAOH) to simultaneously delaminate the layers into highly transparent nano-sized sheets and reduce fluorine content on their surface. Coupling nano-sized and delaminated MXene sheets, mainly terminated by oxygen-containing groups, with TiO₂ results in a photocatalyst with superior photocatalytic activity in NOx oxidation than TiO₂ coupled with conventional MXene or TiO₂-MXene photocatalyst fabricated by thermal treatment of MXene. TiO₂ coupled with delaminated, nanosized MXene converts NO to non-toxic products (i.e., nitrate) and demonstrates high NOx storage selectivity (85 %) and positive DeNOx index (+ 0.215), in contrast to another photocatalyst fabricated by coupling fluorine-containing MXene with TiO₂, which converts NO to toxic NO₂ and demonstrates low NOx storage selectivity (65 %) and negative DeNOx index (-0.055). Furthermore, building upon our efforts to utilize MXene in practical photocatalysis, the third portion of my work demonstrates a one-step, safe, and facile approach to synthesizing titanium carbide MXene with abundant oxygen-containing groups. This process is based on etching the titanium aluminum carbide MAX using sodium hydroxide in the presence of a delaminating agent (hydrazine). Unlike the conventional process, the process does not utilize hazardous hydrofluoric acid and complex tools, opening an avenue for safe and low-cost synthesis of MXene for catalysis, particularly in photocatalytic NOx oxidation reaction where oxygen-containing groups are desired. In addition to CNTs and MXene, graphitic carbon nitride is another promising visible-light-active nanocarbon due to its low cost and ability to form charge carriers under visible light (band gap: ~2.7 eV). However, hybrids formed by coupling g-C₃N₄ and TiO₂ demonstrate only limited activity in NOx oxidation, likely due to their low adsorption capacity. In the fourth part of my work, a macro-mesoporous TiO₂-g-C₃N₄ hybrid is employed as a photocatalyst in NOx oxidation. This porous structure boosts NOx adsorption and storage of NOx oxidation products while enabling visible light absorption. TiO₂-g-C₃N₄ hybrid exhibits high NOx adsorption capacity and converts NO to nontoxic nitrate with minimal formation of NO₂, evident by its positive DeNOx index (+74 ppm) in contrast to g-C₃N₄ with a negative DeNOx (-4 ppm) and TiO₂ with a slightly positive DeNOx index (+ 15 ppm). Consequently, effective NOx photooxidation is achieved by TiO₂-g-C₃N₄ hybrid under visible light. To further investigate the possibility of utilizing TiO₂-nanocarbon in visible-light-driven photocatalysis, the final part of my work exhibits a unique, economical, and scalable approach to synthesize narrow band gap TiO₂-titanium carbide (TiO₂-TiC) photocatalysts. This method is based on detonating a mixture of a hydrocarbon (toluene) and a titanium precursor (titanium tetrachloride) with oxygen in a multi-liter chamber to produce scalable amounts of TiO₂-TiC hybrids. The synthesized TiO₂-TiC shows noticeable NOx photocatalytic activity under visible light. The findings reported in this thesis are expected to boost ongoing efforts to develop efficient TiO₂-based photocatalysts and provide reliable and cost-effective pathways for environmental remediation.
Keywords: Photocatalysis; MXene; Carbon nanotubes; NOx oxidation; Titanium dioxide; Detonation titanium carbide